Let the grandpa's present age be x years and the grandson's present age be y years.
Grandpa's age before 9 years=x-9 years
Grandson's age before 9 years=y-9 years
Given,at that time,Grandpa's age was 9 times the grandson's age.
Grandpa's age after 15 years=x+15 years
Grandson's age after 15 years=y+15 years
Given.at that time,Grandpa's age is 3 times the grandson's age.
it is proved above that x=9y-72.Also x=3y+30
then, also 9y-72=3y+30(proved above)
Grandson's present age=17 years
Grandpa's present age=3y+30=3*17+30=51+30=81 years